Numerical Investigation for Single-Phase and Two-Phase Flow in Duct Banks with Multi Types of Vortex Generators - Adnan Qahtan Ibrahim; Riyadh Sabah Alturaihi (International Journal of Technology, 2023)
This paper examines the numerical work of the thermal convection over tube banks with winglets through the heat exchanger in two parts under turbulent conditions. The first section investigates the influence of two-phase (water and air) flow on the performance of two kinds of vortex generators (Delta and Rectangular) winglets across the oval tube banks. The second section studied the performance of four types of winglets (Delta, Rectangular, Zikzak, and Sinusoidal wavy), circular and oval tubes, forward and downward configurations, and various angles of attack (15°, 20°, and 25°) in two-phase flow. Delta winglets provide the highest performance at an attack angle of 15° for oval tube banks in a two-phase flow with a moderate turbulent flow rate.